2014
DOI: 10.1007/s13197-014-1680-4
|View full text |Cite
|
Sign up to set email alerts
|

Impingement drying for preparing dried apple pomace flour and its fortification in bakery and meat products

Abstract: This study aimed to evaluate impingement drying (ID) as a rapid drying method to dry wet apple pomace (WAP) and to investigate the fortification of dried apple pomace flour (APF) or WAP in bakery and meat products. ID at~110°C reduced the moisture content of apple pomace from 80 % (wet basis) to 4.5 % within 3 h, compared with 24 h to 2.2 % using 40°C forced-air drying and~60 h to 2.3 % using freeze drying. Furthermore, ID enhanced the extractable phenolic compounds, allowing for a 58 % increase in total pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 41 publications
5
50
1
1
Order By: Relevance
“…The application of apple pomace in bakery foods is considered to improve the dietary fiber content and health benefits [27,28]. However, pomace addition results in a decrease in quality and sensory properties of baked products in the majority of cases [29][30][31]. Therefore, efforts have been undertaken to evaluate the effects of apple pomace on each individual bakery product and optimize the utilization level to incorporate.…”
Section: Bakery Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of apple pomace in bakery foods is considered to improve the dietary fiber content and health benefits [27,28]. However, pomace addition results in a decrease in quality and sensory properties of baked products in the majority of cases [29][30][31]. Therefore, efforts have been undertaken to evaluate the effects of apple pomace on each individual bakery product and optimize the utilization level to incorporate.…”
Section: Bakery Productsmentioning
confidence: 99%
“…Moreover, apple pomace has also been reported to be used as a wheat flour substitute in muffins [28,29]. A more recent study by Sudha et al (2016) showed that muffins with less than 20% apple pomace were not only normally symmetrical in shape but also scored highly on sensory tests for color, taste and texture [31].…”
Section: Sweet Bakery Products (Cakes Including Scones and Muffins)mentioning
confidence: 99%
“…So far, PP has not been studied as an ingredient for enriching other related formulations such as sponge and layer cakes. Cakes may be good carriers for these by‐products, thus providing valuable healthy components to the diet (Jung et al ., ; Younas et al ., ; Bajerska et al ., ; Khalifa et al ., ; Mildner‐Szkudlarz et al ., ). However, it must be taken into account that the physical properties of pomace and mainly its particle size may influence the technological quality of the final product (De la Hera et al ., ; Dhen et al ., ; Majzoobi et al ., ).The objectives of the present work were to assess ground PP as a rich fibre ingredient for sponge and layer cakes.…”
Section: Introductionmentioning
confidence: 99%
“…Fibre incorporation resulted in less cooking loss and an increase in sausage hardness (Choi et al, 2016). Dietary fibre is a source of valuable pectin and dietary fibre from apple pomace that are successfully transferred to meat products, lowering hardness and springiness (Jung et al, 2015). Fibre incorporation increases the stability of emulsions because water can be bound to insoluble polysaccharides forming an insoluble three-dimensional net increasing the consistency of the continuous phase of meat emulsions, improving water and fat retention (Cava et al, 2012).…”
Section: Textural Profile Analysismentioning
confidence: 99%